Exploring the Mesoamerican subterranean realm - Brady, James E., editor; Verdugo, Cristina, editor; University Press of Colorado, publisher (Colorado State University. Libraries, 2025)
This essay collection explores the ritual use of caves in Mesoamerica by the Maya and other cultural groups, including research from central Mexico as well as the Yucatán.--Provided by publisher.
Introduction to Exploring the Mesoamerican Subterranean Realm / James E. Brady and Cristina Verdugo -- Turning a Critical Eye on the History of Maya Cave Archaeology: the Emergence of the Discipline in its Current Form / Ann M. Scott -- The Cave of Balankanché, Yucatán, México, Revisited: 1959-2019 / William J. Folan -- Confronting Archaeology's Ambivalence with a Constructed Subterranean: a Critical Reassessment of the Underground in the Northern Lowlands / James E. Brady [and five others] -- The Inadequacy of the "Chultun" Category / Thomas Ruhl -- The Cerro de la Estrella and the Politics of Time / Ismael Arturo Montero García, Christophe Helmke, and James E. Brady -- Invisible Ritual: Chemical Residue Analysis of Excavated Soils from the Cave beneath the Sun Pyramid, Teotihuacan / Rebecca Sload -- "Tlaloc" and "Chicomoztoc" in the North: Evidence for Mesoamerican Chthonic Cosmovision in the United States Southwest and Northwest Mexico / Scott Nicolay, Margaret Berrier, and Myles Miller -- Caves in Ancient Maya Pilgrimage: Archaeological Evidence of a Multifaceted Role / James E. Brady -- A History of Speleoarchaeological Investigations at Yaxchilan, Mexico / Christopher Helmke, Ileana Echauri Pérez, and Eduardo Arturo Tejeda Monroy -- Caves and the Question of Sacrifice: Changing the Rules of Engagement / Cristina Verdugo and James E. Brady.
Keywords: Indians of Mexico -- Rites and ceremonies; Indians of Central America -- Rites and ceremonies; Mayas -- Rites and ceremonies; Caves -- Religious aspects; Indians of Central America -- Religion; Mayas -- Religion